2006
DOI: 10.1158/1535-7163.mct-05-0465
|View full text |Cite
|
Sign up to set email alerts
|

Enzastaurin (LY317615), a protein kinase Cβ inhibitor, inhibits the AKT pathway and induces apoptosis in multiple myeloma cell lines

Abstract: Enzastaurin (LY317615), an acyclic bisindolylmaleimide, is an oral inhibitor of the protein kinase CB isozyme. The objective of this study was to assess the efficacy of enzastaurin in inducing apoptosis in multiple myeloma (MM) cell lines and to investigate possible mechanisms of apoptosis. Cell proliferation assays were done on a variety of MM cell lines with unique characteristics (dexamethasone sensitive, dexamethasone resistant, chemotherapy sensitive, and melphalan resistant). The dexamethasonesensitive M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 18 publications
6
45
0
1
Order By: Relevance
“…Enzastaurin also reduced the phosphorylation of the downstream PKCb-signaling pathway effectors Akt and GSK3b; these findings are consistent with several previous reports in different cancer cell lines, xenografts and peripheral blood mononuclear cells (PBMCs) (Graff et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006), suggesting the use of GSK3b phosphorylation in PBMCs as a pharmacodynamic marker for enzastaurin (Graff et al, 2005). Our experiments showed that the Akt pathway can also be affected by pemetrexed, as reported previously (Giovannetti et al, 2005(Giovannetti et al, , 2008.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Enzastaurin also reduced the phosphorylation of the downstream PKCb-signaling pathway effectors Akt and GSK3b; these findings are consistent with several previous reports in different cancer cell lines, xenografts and peripheral blood mononuclear cells (PBMCs) (Graff et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006), suggesting the use of GSK3b phosphorylation in PBMCs as a pharmacodynamic marker for enzastaurin (Graff et al, 2005). Our experiments showed that the Akt pathway can also be affected by pemetrexed, as reported previously (Giovannetti et al, 2005(Giovannetti et al, , 2008.…”
Section: Discussionsupporting
confidence: 93%
“…Enzastaurin was originally evaluated in human tumour xenograft-bearing mice for its antiangiogenic activity upon PKCb inhibition, as it showed reduction of plasma VEGF levels together with a significant decrease in intratumoural vessel density (Keyes et al, 2004). However, several studies have shown that enzastaurin exhibits direct growth inhibiting effects on a wide array of cultured human tumour cells (Graff et al, 2005;Oberschmidt et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Podar et al, 2007;Spalding et al, 2007;Lee et al, 2008). Recent studies suggest that the antitumour effects of enzastaurin are mediated through interference with the phosphatidylinositol 3-kinase (PI3K)/Akt pathway (Graff et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Lee et al, 2008), an important pathway regulating the apoptotic response.…”
mentioning
confidence: 99%
“…Enzastaurin also has direct effects on tumor cell growth, survival and invasion (Graff et al, 2005;Rizvi et al, 2006). Enzastaurin inhibited the growth of primary melanoma cultures and had a preferential growth inhibitory effect on uveal melanoma cell lines with GNAQ mutations (Hanauske et al, 2007;Wu et al, 2012).…”
Section: Protein Kinase C Inhibitors As Therapeutics For Melanomamentioning
confidence: 99%
“…Because glucocorticoids are potent inducers of apoptosis in myeloma cells, we screened additional MM chemotherapeutic agents including 2-methoxyestradiol, all-trans retinoic acid (ATRA), enzastaurin, rapamycin, and thalidomide to determine if GILZ up regulation was observed upon induction of apoptosis in myeloma cells by a variety of agents [37][38][39][40][41]. Despite inducing apoptosis in MM.1S cells, none of these drugs up regulated GILZ in our screen.…”
Section: Gilz Is Up Regulated By Inhibiting the Pi3-kinase/akt Pathwaymentioning
confidence: 99%